2011
DOI: 10.1007/s10681-011-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure composed of additive QTL, epistatic QTL pairs and collective unmapped minor QTL conferring oil content and fatty acid components of soybeans

Abstract: The relative importance of various types of quantitative trait locus (QTL) conferring oil content and its fatty acid components in soybean seeds was assessed through testing a recombinant inbred line (RIL) population (derived from KF1 9 NN1138-2) in randomized blocks experiments in [2004][2005][2006]. The contents of oil and oleic, linoleic, linolenic, palmitic and stearic acids were determined with automatic Soxhlet extraction system and gas chromatography, respectively. Based on the established genetic linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 43 publications
4
26
1
Order By: Relevance
“…4 (continued) The importance of epistatic effect QTL has been documented for various traits in rice [44][45][46][47][48], wheat [49][50][51], and soybean [52], demonstrating that both main effect and epistatic QTL are underlying various quantitative traits in plants. The negative correlation of lignin content and sugar release observed in this population suggests that some segregants or natural variants with reasonably low lignin content and above average sugar release may be identified through selection.…”
Section: Lig9am2mentioning
confidence: 99%
“…4 (continued) The importance of epistatic effect QTL has been documented for various traits in rice [44][45][46][47][48], wheat [49][50][51], and soybean [52], demonstrating that both main effect and epistatic QTL are underlying various quantitative traits in plants. The negative correlation of lignin content and sugar release observed in this population suggests that some segregants or natural variants with reasonably low lignin content and above average sugar release may be identified through selection.…”
Section: Lig9am2mentioning
confidence: 99%
“…(Wilson et al 2001;Monteros et al 2008;Ha et al 2010;Li et al 2011;Chen et al 2012) and olive (Olea europaea L.) (Poghosyan et al 1999;Hernández et al 2005;Banilas et al 2011). With respect to genes involved in the fatty acid biosynthesis in oil palm, Nakkaew et al (2008) identified and cloned the gene of biotin carboxylase (accD) from E. guineensis which is involved in the first step of the fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Though all the QTL were of minor effect, we saw some positional overlap with published QTL for seed linolenic acid. Li et al (2011) identified an association between Satt537 and seed linolenic acid content on chromosome 2 at nearly the same map position as q.2n (within 5 cM). In the same study, a QTL was identified on chromosome 4, however it was not in the same region as q.4n .…”
Section: Resultsmentioning
confidence: 84%
“…The two QTL identified on chromosome 2 accounted for 13.75 and 7.86% of the variation in seed stearic acid content. QTL associated with stearic acid have been previously reported on chromosome 2 within 5 cM of q.2.1s (Li et al 2011; Xie et al 2011). On chromosome 4, the 194D allele contributed to elevated stearic acid.…”
Section: Resultsmentioning
confidence: 97%